Development of DNA vaccine containing HN and F genes of Newcastle disease virus and its efficacy following in vivo and in ovo immunizations - Firouzamandi, Masoumeh (2013)
Newcastle disease is a fatal viral disease which is highly contagious that affects most species of birds and is a major economic threat in the poultry industry. Both the HN and F glycoproteins of Newcastle disease virus (NDV) are essential for pathogenicity and virus infectivity. Though vaccines are available for the control of the disease but the vaccine with more efficacies is still required. The third generation vaccines, which include DNA vaccine, have the potential to be safer and more efficacious. In this study, DNA vaccines developed successfully by using the HN and F genes from a Malaysian viscerotropic velogenic AF2240 NDV strain into the pIRES bicistronic mammalian expression vector separately and combined.Three recombinant plasmids were constructed with the Kozak translation initiation sequences, namely, pIRES/HN, pIRES/F and pIRES/HN/F. The HN and F genes in the pIRES vector has been expressed and tested successfully using the indirect immunofluore scence (IIF) test and Western blotting in the Vero cell line (in vitro). The results of IIF showed that all the DNA-transfected cells exhibited bright cytoplasmic fluorescence, indicating both the F and HN proteins were successfully expressed in the mammalian cell line. Also, Western blotting results revealed the expected bands of size approximately 74kDa, 55 kDa and 12 kDa for HN, F1 and F2, respectively. In vivo experiment I showed that single vaccination with the plasmid DNA (pDNA) was not sufficient to induce antibody titer in specific pathogen free (SPF) chickens. Whereas, single pDNA vaccination and boosted by killed vaccine, showed a significant difference in ELISA antibody levels (p<0.05) elicited by either monocistronic (pIRES/HN + pIRES/F) or bicistronic (pIRES/HN/F) plasmids at one week post booster, compared with the killed vaccine alone. However, the HI titer was not significant higher (p>0.05) in vaccinated chickens with pIRES/HN/F and pIRES/HN+pIRES/F which boosted with killed vaccine at one week post booster compared with vaccinated chicken with killed vaccine alone. Overall, it was concluded that the recombinant pDNA vaccine can be used to increase the efficacy of the killed vaccine immunization procedure. In vivo experiment II showed that twice vaccination with pDNA was able to elicit significant antibody titers (p< 0.05) by either monocistronic or bicistronic plasmid, after one week of second pDNA vaccination (booster). The results proposed that DNA immunization of chickens at second vaccination had enhanced the antibody response successfully. As a result, the findings of the present study well demonstrated that vaccination with the co-expression plasmid pIRES/HN/F can induce a stronger antibody response thanvaccination with pIRES/HN or pIRES/F alone. In ovo vaccination with 10 μg pDNA/egg was not sufficient to induce production of antibody in SPF chickens. However, in ovo vaccination with 40 μg pDNA/egg induced high levels of antibody titer (p<0.05) in SPF chickens at four weeks post vaccination. The findings also showed that vaccination with 40 μg pDNA/egg able to confer protection against ND in two out of seven SPF chickens. Although, the chickens produced antibody titres three weeks post in ovo vaccination, it was not sufficient to protect the chickens from lethal viral challenge. However, vaccination with pDNA/Dextranspermine complex did not induce high antibody titer compared with naked pDNA. In conclusion, DNA vaccination with pIRES/HN/F is suitable for in vivo application but not encourage for in ovo use. More studies are required to investigate how to increase the efficacy of the constructed recombinant pDNA vaccines.